Does Sharia Investment Knowledge and Investment Experience on Choosing Sharia Mutual Fund Investment Through the Investor Lifestyle - Santi Arafah; Yunanda Eka Putra; Iskandar Muda; Andri Soemitra; Yusrizal (MALIA: Jurnal Ekonomi Islam, 2025)
Introduction: This research aims to determine the effect of Sharia investment knowledge and investment experience in choosing Sharia mutual fund investment. Sharia investment has an important role in economic development, in the form of job creation, increasing income and purchasing power, equitable economic circulation and increasing gross domestic product (GDP). Methods: The sample in this research were 100 investors registered with the Indonesia Stock Exchange. The data analysis technique used in this research uses SEM-PLS analysis techniques. Results: The results of the research conducted with a confidence level of 95% based on sig. 5%, stating that sharia investment knowledge, investment experience and lifestyle effect decision making in choosing Sharia mutual fund investment. Conclusion and suggestion: investors must have a good understanding of sharia investment knowledge and investment experience that is harmonized with the lifestyle of investors in investing in Sharia mutual funds in order to avoid future losses and in order to provide good benefits in the present and future